Hacked - Non-existing Tribe, Gets Lost - Kresalek, Dávid (Hungary, 2007)
The film is the media hack phenomenon but it is also a snapshot of a young Central-European democracy and the press relations in today’s Hungary. There are two strands in the film. In the first one we can see traditional interviews with the journalists and editors in chief of the largest Hungarian online and offline newspapers. They talk about the press that came into being after the change of the political system, the birth of tabloid papers in Hungary and their status as well as the media hack phenomenon. At the same time, we can follow up a real media hack from scratch to realization and exposure. Our main goal is to show the operating mechanisms of the media and we believed a media hack would be the best way to test the press. Apart from this we would like to draw attention to awareness as media consumers so that we do not believe everything we read or hear in the media.
Verzio Film Festival Submission
Keywords: Documentary films